2008
DOI: 10.1158/1078-0432.ccr-07-4054
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Elevated Gene-1 is a Novel Prognostic Marker for Breast Cancer Progression and Overall Patient Survival

Abstract: Purpose: The present study was aimed at clarifying the expression of astrocyte elevated gene-1 (AEG-1), one of the target genes of oncogenic Ha-ras, in breast cancer and its correlation with clinicopathologic features, including the survival of patients with breast cancer. Experimental Design: The expression of AEG-1 in normal breast epithelial cells, breast cancer cell lines, and in four cases of paired primary breast tumor and normal breast tissue was examined using reverse transcription-PCR and Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
311
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(337 citation statements)
references
References 24 publications
24
311
2
Order By: Relevance
“…Overexpressed LYRIC/AEG-1 reduces PLZF-mediated repression by abrogating the ability of PLZF to bind DNA, perhaps by sequestering PLZF to nuclear bodies. LYRIC/AEG-1 has been shown to be overexpressed during tumourigenesis (Li et al, 2008;Hu et al, 2009;Thirkettle et al, 2009) and our results suggest that this may lead to a reduction in PLZF-mediated repression. This would increase oncogene expression such as c-myc and a decrease in genes involved in apoptosis (Bernardo et al, 2007) (Figure 4d).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Overexpressed LYRIC/AEG-1 reduces PLZF-mediated repression by abrogating the ability of PLZF to bind DNA, perhaps by sequestering PLZF to nuclear bodies. LYRIC/AEG-1 has been shown to be overexpressed during tumourigenesis (Li et al, 2008;Hu et al, 2009;Thirkettle et al, 2009) and our results suggest that this may lead to a reduction in PLZF-mediated repression. This would increase oncogene expression such as c-myc and a decrease in genes involved in apoptosis (Bernardo et al, 2007) (Figure 4d).…”
supporting
confidence: 55%
“…LYRIC/ AEG-1 is reported to be regulated by HA-RAS and c-myc (Lee et al, 2006), to suppress activators of apoptosis such as FOXO3a (Kikuno et al, 2007), and to activate nuclear factor-kB which regulates the expression of cell adhesion molecules implicated in cancer progression and metastasis . Recently, it has been shown that LYRIC/AEG-1 is overexpressed in breast and prostate tumourigenesis (Li et al, 2008;Hu et al, 2009;Thirkettle et al, 2009). We have shown that in benign prostate tissue LYRIC/ AEG-1 is localized predominantly in the nucleus and that loss of nuclear LYRIC/AEG-1 in cancer results in poor survival (Thirkettle et al, 2009).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…AEG‐1/MTDH was subsequently found to mediate the metastasis of breast cancer 8. In recent years, AEG‐1 expression was found to be elevated and correlated with clinical tumour type, stage, metastasis and prognosis in a variety of cancers, including breast 9, lung 10, colorectal 11, cervical 12, 13, head and neck 14, hepatocellular 15 and gastric cancers 16, 17. AEG‐1 has been shown to be transcriptionally up‐regulated by Ha‐Ras‐activated PI3K and c‐Myc 18.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a newly identified astrocyte elevated gene-1 (AEG-1), originally discovered as a protein induced in primary human fetal astrocytes infected with HIV-1 or treated with HIV gp120 or tumor necrosis factor-a, was implicated in promotion of oncogenesis, abrogation of cancer cell apoptosis and induction of metastasis (Kang et al, 2005;Emdad et al, 2006Emdad et al, , 2007Lee et al, 2006Lee et al, , 2008Kikuno et al, 2007;Ash et al, 2008;Li et al, 2008;Sarkar et al, 2008). It was found that ectopic expression of AEG-1 could augment anchorage-independent growth of nontumorigenic melanocytes and astrocytes (Kang et al, 2005;Emdad et al, 2007).…”
Section: Introductionmentioning
confidence: 99%